Heidi - Illustrated by Leplar, Anna C. (London Ladybird)
Read It Yourself book and CD packs are a series of traditional tales, graded in a simple way to ensure a successful start to reading. Four different levels encourage children to develop reading confidence and essential vocabulary. Children will love listening to the story on CD and following along with the text in their book. 4-7 yrs.
Include Color Illustrations
Keywords: Children's stories